DESIGNING THE ACCOUNTING PROFESSIONAL CODE OF ETHICS BASED ON THE LOCAL WISDOM OF THE GAYO COMMUNITY - Ramdansyah Fitrah; Saparuddin Siregar (Jurnal Akuntansi dan Pajak, 2022)
The accountant's code of ethics provides accountants with dealing with clients, the public, and other accountants. Although there is already a code of ethics that regulates the accounting profession, cases of violations of professional ethics involving accountants still occur. The concept of ethics cannot be just a standard of professional code of ethics, and ethics must be full of values and meanings. Ethics is found in culture because culture is a value rooted in people's lives to regulate the order of people's lives themselves. The local wisdom value system of the Gayo community has a conventional value system: mukemel (self-esteem), tertip (orderly), setie (faithful), semayang-gemasih (affection), mutentu (useful), amanah (trustworthy), genap mupakat (colloquy), alang tulung (help each other), and bersikekemelen (competitive). The results show that the Gayo community's conventional value system is relevant to the basic principles of professional accountant ethics. Mutentu values are relevant to the principle of integrity, amanah values are relevant to the principle of objectivity and professional competence and due care, setie values are appropriate to maintaining confidentiality, and tertip values are relevant to the principles of professional behavior. Meanwhile, the values of semayang gemasih, alang tulung, genap mupakat, and bersikekemelen are the basic values that form the foundation for the values of mutentu, amanah, setie and tertip. Furthermore, mukemel value is the final behavior expected from an accountant as a manifestation professional accountant ethics.